A novel homozygous variant in the SMOC1 gene underlying Waardenburg anophthalmia syndrome. (4th July 2017) - Ullah, Asmat; Umair, Muhammad; Ahmad, Farooq; Muhammad, Dost; Basit, Sulman; Ahmad, Wasim
ABSTRACT: Background : Waardenburg anophthalmia syndrome (WAS), also known as ophthalmo-acromelic syndrome or anophthalmia-syndactyly, is a rare congenital disorder that segregates in an autosomal recessive pattern. Clinical features of the syndrome include malformation of the eyes and the skeleton. Mostly, WAS is caused by mutations in the SMOC-1 gene. Materials and methods : The present report describes a large consanguineous family of Pakistani origin segregating Waardenburg anophthalmia syndrome in an autosomal recessive pattern. Genotyping followed by Sanger sequencing was performed to search for a candidate gene. Results : SNP genotyping using AffymetrixGeneChip Human Mapping 250K Nsp array established a single homozygous region among affected members on chromosome 14q23.1-q24.3 harboring the SMOC1 gene. Sequencing of the gene revealed a novel homozygous missense mutation (c.812G>A; p.Cys271Tyr) in the family. Conclusion : This is the first report of Waardenburg anophthalmia syndrome caused by a SMOC1 variant in a Pakistani population. The mutation identified in the present investigation extends the body of evidence implicating the gene SMOC-1 in causing WAS.